An EEG coherence-based analysis approach for investigating response conflict processes in 7 and 9-year old children - Almabruk, Tahani A A; Iyer, Kartik; Tan, T.; Roberts, G.; Anderson, M. (IEEE, 2015)
Understanding the development of the brain's neural networks can reveal critical insights into the cognitive changes that occur from infancy to late childhood. Behavioural metrics including: task accuracy, stimuli recognition, and reaction time show dramatic changes over childhood. In this study we investigated response control using the Erikson Flanker task. In a dataset of 45 EEG recordings, we calculated spectral coherence to measure connectivity between all possible electrode pairs. Coherence measures were performed on two different trial conditions -congruent (where there is no response conflict) and incongruent (where response conflict is induced). The increase in incongruent coherence compared to the congruent was investigated for each electrode pair over 45 healthy subjects aged seven years. The same calculation was then performed on the same group of subjects two years later when they were aged nine years. The results revealed that at age seven years, increased coherence was detected in the left prefrontal to right and left parieto-occipital - i.e. an anatomical region located between the parietal and occipital lobes - within theta band. No increase was found for the older group-at age nine years- which may indicate cognitive development in conflict processing mechanism.